Towards Investor Confidence Insider Trading Laws and its Implications on Market Efficiency-Part 2 - Valera, Karla Regina D.; Velasco-Lao, Francesca Marie (Philippine Law Journal; Vol 84 No 2 (2010))
No abstract.